2023
DOI: 10.1097/md.0000000000034895
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy and safety of duloxetine for the treatment of patients after TKA or THA: A systematic review and meta-analysis

Yongqiang Zhou,
Xiao Chen,
Chang Chen
et al.

Abstract: Background: Duloxetine, a serotonin–norepinephrine dual reuptake inhibitor, may improve analgesia after total joint arthroplasty (TJA). However, there is still no consensus on its effectiveness and safety. We conducted the meta-analysis to investigate the analgesic effect and safety of duloxetine for the treatment of patients received total knee or hip arthroplasty. Methods: Pubmed, Cochrane Central Registry for Clinical Trials, Embase, OVID, Web of Sci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 48 publications
0
1
0
Order By: Relevance
“…Data on the analgesic effectiveness of duloxetine differ among the studies discussed: Yang et al reported a significant reduction in pain in the range from three days to eight weeks after the procedure, while Zhou et al noted the above effect only within the first 24h after surgery. In all the mentioned works, the authors pointed to the small amount of material available for analysis, and therefore reported the need to conduct further, large, well-designed RCTs [32][33][34]. In another metaanalysis assessing the effectiveness of duloxetine for postoperative pain control after total knee or hip arthroplasty, Jones et al reported a reduction in opoid consumption 48 and 72h after surgery in patients taking the drug.…”
Section: Discussionmentioning
confidence: 99%
“…Data on the analgesic effectiveness of duloxetine differ among the studies discussed: Yang et al reported a significant reduction in pain in the range from three days to eight weeks after the procedure, while Zhou et al noted the above effect only within the first 24h after surgery. In all the mentioned works, the authors pointed to the small amount of material available for analysis, and therefore reported the need to conduct further, large, well-designed RCTs [32][33][34]. In another metaanalysis assessing the effectiveness of duloxetine for postoperative pain control after total knee or hip arthroplasty, Jones et al reported a reduction in opoid consumption 48 and 72h after surgery in patients taking the drug.…”
Section: Discussionmentioning
confidence: 99%